Scatter radiation exposure during mobile X-Ray examinations - Abrantes, António (2022)
The main goal of this research was to quantify scatter radiation exposure from mobile x-ray examinations. The simulation consisted of reproducing the technical conditions for the chest anteroposterior (AP) examination in supine and semi-supine positions as well as for the abdomen tangential projection, using a full body anthropomorphic phantom and an x-ray detector. For distances above 1m, the national dose limits for exposed workers is not exceeded (12 mSv/year), but for members of the public it is exceeded (2 mSv/year). Therefore, exposed workers should use a personal dosimeter, employ protective measures and stand behind the mobile equipment. The use of ionising radiation for diagnostic and treatment purposes has increased due to the development of new equipment and easier access to radiologic examinations.